2022
DOI: 10.1002/ijgo.14418
|View full text |Cite
|
Sign up to set email alerts
|

Counseling for stress urinary incontinence in the era of adverse publicity around mesh usage: Results from a large‐sample global survey

Abstract: Stress urinary incontinence (SUI) is a common cause of urinary incontinence, negatively affecting a woman's quality of life. One in four women will have SUI during their lifetime and it has been estimated that surgical procedures for SUI are likely to increase by 50% from 210 700 cases in 2010 to 310 050 cases in 2050 in the USA. 1,2 The mid-urethral sling (MUS) is a polypropylene monofilament of proven efficacy and safety in clinical trials and everyday practice. [3][4][5]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several factors may have led to this including: the rulings by the FDA in 2011 banning mesh in the United States; the ruling by the MHRA in the UK in 2011 and 2012 raising awareness on the debilitating complications of the mesh; and the reports from the National Institute for Clinical Excellence between 2007 and 2017, where caution was urged in the use of mesh and a focus for more research was encouraged. But, perhaps it was the rise in public awareness led by women affected by the complications of mesh along with the national media that changed the emphasis from mesh insertion and its benefits, to that of mesh complications and the need for surgical removal [39,40]. Unsurprisingly, this was mirrored in the rise of both medico-legal claims against implanting surgeons, device firms and institutions of practice [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may have led to this including: the rulings by the FDA in 2011 banning mesh in the United States; the ruling by the MHRA in the UK in 2011 and 2012 raising awareness on the debilitating complications of the mesh; and the reports from the National Institute for Clinical Excellence between 2007 and 2017, where caution was urged in the use of mesh and a focus for more research was encouraged. But, perhaps it was the rise in public awareness led by women affected by the complications of mesh along with the national media that changed the emphasis from mesh insertion and its benefits, to that of mesh complications and the need for surgical removal [39,40]. Unsurprisingly, this was mirrored in the rise of both medico-legal claims against implanting surgeons, device firms and institutions of practice [41].…”
Section: Discussionmentioning
confidence: 99%
“…2021 position statement that "Polypropylene mesh slings are the standard of care for the surgical treatment of SUI." 3,4 Patient hesitation is likely related to recovery restrictions, potential complications with mesh usage, as well ambivalence toward surgery for a non-life-threatening condition. 5 Recently updated American Urological Association guidelines revised promoting MUS as first-line surgical treatment stating, "patients should be offered all viable options for treatment of their stress incontinence, with a discussion that includes detailed counseling regarding the risks, benefits, alternatives to each approach, and the safety and efficacy profiles of the various choices."…”
Section: Why This Mattersmentioning
confidence: 99%
“…The midurethral sling (MUS) offers an outpatient procedure to treat SUI with high efficacy, low complication rates, and fast recovery times. This practice is supported by organizations such the American Urogynecologic Society and the Society of Urodynamics, Female Pelvic Medicine and Urogenital Reconstruction who wrote in a 2021 position statement that “Polypropylene mesh slings are the standard of care for the surgical treatment of SUI.” 3,4 Patient hesitation is likely related to recovery restrictions, potential complications with mesh usage, as well ambivalence toward surgery for a non–life-threatening condition 5 . Recently updated American Urological Association guidelines revised promoting MUS as first-line surgical treatment stating, “patients should be offered all viable options for treatment of their stress incontinence, with a discussion that includes detailed counseling regarding the risks, benefits, alternatives to each approach, and the safety and efficacy profiles of the various choices.” 6 …”
mentioning
confidence: 99%
“…Data from the National Health Service (NHS) in England between 2012 and 2018 showed a decrease in mid-urethral sling surgery and an increase in bulking procedures [ 18 ]. An electronic survey of the members of the International Urogynecological Association (IUGA) and the American Urogynecologic Society (AUGS) showed that retropubic mid-urethral slings were the preferred initial surgical treatment for SUI (62%), whereas bulking agents were only preferred by 5% of the survey responders [ 52 ]. Another survey among healthcare professionals in England showed that using mid-urethral slings for treating SUI was still the most popular choice before and after informing of specific complications [ 53 ].…”
Section: Bulking Agents To Treat Suimentioning
confidence: 99%